Analisis Pengaruh Current Ratio, Return On Assets, Debt Equity Ratio, dan Cash Position Terhadap Dividen Payout Ratio pada Perusahaan Manufaktur Industri Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia Selama Periode 2015-2017 - Rosmeilani Christina Marintan Tiurma; Indra Widjaja (Universitas Tarumanagara, 2020)
The research aimed to determine the effect of Current Ratio (CR), Return on Assets (ROA), Debt Equity Ratio (DER) and Cash Position (CP), against the Dividend Payout Ratio (DPR) on manufacturing companies specially in consumption sector In Indonesia Stock Exchange for period 2015-2017. This study also purposes to determine the effect of Current Ratio (CR), Return on Assets (ROA), Debt Equity Ratio (DER) and Cash Position (CP) simultaneous against the Dividend Payout Ratio (DPR). This research was used a causal associative method by taking secondary data. The selection of sample used purposive sampling method. From the predetermined criteria obtained a sample of 13 companies. Analysis using SPSS Program.Based on statistical t test, the result of the research shows that Return on Assets (ROA) had a significant, negative effect on Dividend Payout Ratio (DPR). Meanwhile, other variables like Current Ratio (CR), Debt to Equity Ratio (DER) and Cash Position (CP) did not affect the Dividend Payout Ratio (DPR). Based on F test indicates that variables Current Ratio (CR), Return on Assets (ROA), Debt to Equity Ratio (DER) and Cash Position (CP) simultaneously affect Dividend Payout Ratio (DPR) on manufacturing companies on consumption sector listed in Indonesia Stock Exchange for period 2015-2017.